MODEL ALTERNATIF PENDIDIKAN ISLAM TRANSFORMATIF (Studi Nilai-Nilai Pendidikan Islam dalam Tradisi Ambengan Pada Peringatan Hari Besar Islam di Desa Brunorejo Purworejo) - Dadan Ridwan (Millah: Journal of Religious Studies, 2016)
This paper critically describe and analyze the educational values   of Islam contained in Ambengan tradition held in the village Brunorejo, Bruno, Purworejo. Ambengan tradition in the village of Brunorejo can be used as a medium of education Islam transformative. The values contained in the Islamic Education in Ambengan tradition is the educational value of faith, the value of moral education and social educational value. These educational values   contained within the symbols contained in equipment implementation in Ambengan tradition and it’s the procession. The educational values that have deep meaning as the local wisdom expected to be able to reduce radicalism included in public life today. As a  result of a culture based on religion, it is expected to be able to continue to be developed as a medium for the internalization of values education in the community. So it will be able to be absorbed and translated in public life.